An alkaline active feruloyl-CoA synthetase from soil metagenome as a potential key enzyme for lignin valorization strategies - Sodré, Victoria; Araujo, Juscemácia Nascimento; Augusto Gonçalves, Thiago; Vilela, Nathália; Kimus Braz, Antonio Sergio; Franco, Telma Teixeira; de Oliveira Neto, Mário [UNESP]; de Lima Damasio, André Ricardo; Garcia, Wanius; Squina, Fabio Marcio (Public Library of Science (PLoS), 2019)
Ferulic acid (FA), a low-molecular weight aromatic compound derived from lignin, represents a high-value molecule, used for applications in the cosmetic and pharmaceutical industries. FA can be further enzymatically converted in other commercially interesting molecules, such as vanillin and bioplastics. In several organisms, these transformations often start with a common step of FA activation via CoA-thioesterification, catalyzed by feruloyl-CoA synthetases (Fcs). In this context, these enzymes are of biotechnological interest for conversion of lignin-derived FA into high value chemicals. In this study, we describe the first structural characterization of a prokaryotic Fcs, named FCS1, isolated from a lignin-degrading microbial consortium. The FCS1 optimum pH and temperature were 9 and 37C, respectively, with Km of 0.12 mM and Vmax of 36.82 U/mg. The circular dichroism spectra indicated a notable secondary structure stability at alkaline pH values and high temperatures. This secondary structure stability corroborates the activity data, which remains high until pH 9. The Small Angle X-Ray Scattering analyses resulted on the tertiary/quaternary structure and the low-resolution envelope in solution of FCS1, which was modeled as a homodimer using the hyperthermophilic nucleoside diphosphate-forming acetyl-CoA synthetase from Candidatus Korachaeum cryptofilum. This study contributes to the field of research by establishing the first biophysical and structural characterization for Fcs, and our data may be used for comparison against novel enzymes of this class that to be studied in the future.